2020
DOI: 10.1096/fj.202000892r
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the PI 3‐kinase pathway disrupts the unfolded protein response and reduces sensitivity to ER stress‐dependent apoptosis

Abstract: Class Ia phosphoinositide 3‐kinases (PI3K) are critical mediators of insulin and growth factor action. We have demonstrated that the p85α regulatory subunit of PI3K modulates the unfolded protein response (UPR) by interacting with and regulating the nuclear translocation of XBP‐1s, a transcription factor essential for the UPR. We now show that PI3K activity is required for full activation of the UPR. Pharmacological inhibition of PI3K in cells blunts the ER stress‐dependent phosphorylation of IRE1α and PERK, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…In model mice of obesity and diabetes, however, insulin-mediated nuclear translocation of XBP-1 s protein is impaired due to insulin resistance [25,26]. A similar insulin signaling-mediated nuclear translocation of XBP-1 s protein was recently reported in other tissues as well [27]. Interestingly, XBP-1 s protein regulates gluconeogenesis rather directly, via ubiquitination and consequent proteasome-mediated degradation of FoxO1, a transcription factor involved in the induction of gluconeogenic enzymes in the liver [28] (Figure 3).…”
Section: Er Stress and Metabolic Disorderssupporting
confidence: 71%
“…In model mice of obesity and diabetes, however, insulin-mediated nuclear translocation of XBP-1 s protein is impaired due to insulin resistance [25,26]. A similar insulin signaling-mediated nuclear translocation of XBP-1 s protein was recently reported in other tissues as well [27]. Interestingly, XBP-1 s protein regulates gluconeogenesis rather directly, via ubiquitination and consequent proteasome-mediated degradation of FoxO1, a transcription factor involved in the induction of gluconeogenic enzymes in the liver [28] (Figure 3).…”
Section: Er Stress and Metabolic Disorderssupporting
confidence: 71%
“…SHORT syndrome (short stature, hypermobility of joints, ocular depression, Rieger's anomaly, teething delay) with partial lipodystrophy, is caused by a hot spot mutation in PIK3R1 which has a central role in the insulin‐signaling pathway and growth factor resistance 246–248 . Mutation carriers of the dominant‐negative mutation in PIK3R1 seem to be protected from obesity and hepatic steatosis but not diabetes, 249 and the disease mechanisms is associated with unfolded protein response and reduced sensitivity to ER stress‐dependent apoptosis 250 …”
Section: Monogenic Insulin Resistance Syndromesmentioning
confidence: 99%
“…[246][247][248] Mutation carriers of the dominant-negative mutation in PIK3R1 seem to be protected from obesity and hepatic steatosis but not diabetes, 249 and the disease mechanisms is associated with unfolded protein response and reduced sensitivity to ER stress-dependent apoptosis. 250 The mainstay of therapy for lipodystrophy is dietary intervention with a low-fat, calorie-neutral diet, 241 and an expert dietician as part of the multidisciplinary team is of paramount importance. In partial lipodystrophy, insulin sensitizers such as metformin and glitazones may be initially effective 251 but glitazones may exacerbate accumulation of ectopic fat in the face and neck.…”
Section: Monogenic Lipodystrophiesmentioning
confidence: 99%
“…Mounting evidence have suggested that the genetic alterations of classical cellular signaling pathways can also trigger ERS, and the three parallel yet distinctive UPR pathways interplay with them to determine oncogenic transformation and cell fate. For example, in brown adipocytes of hepatocellular carcinoma (HCC), the inhibition of the PI3K/AKT pathway leads to decreased levels of PERK phosphorylation; downregulates the expression of ATF4 and CHOP; decreases the phosphorylation levels of IRE1, GRP78, and XBP1; and antagonizes the effects of the ERS inducer tunicamycin (Winnay et al, 2020). In addition, PI3K/AKT has been found to positively regulate UPR in a lung fibrosis model (Hsu et al, 2017).…”
Section: Association Between Upr Pathway and Classical Signaling Pathwaysmentioning
confidence: 99%